Pengaruh SSRIs Untuk Meningkatkan Independensi Fungsional Pada Pasien Depresi Pasca Stroke: Effect of SSRIs to Improve Functional Independence in Post-Stroke Depression Patients - Winda Puspita Salim; Yetty Octavia Hutahaean; Fransiska Anggreni Sihotang (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Post-stroke depression has a negative impact on the functional independence of patients carrying out daily activities. Selective serotonin reuptake inhibitors (SSRIs) are a class of antidepressants that are recommended as the first-line therapy for post-stroke depression because of their favorable tolerability profile. This literature review is intended to present a new insight about the effect of SSRIs in increasing the functional independence in patients with post-stroke depression. We applied a qualitative research design using two notable databases: PubMed and Google Scholar. Only references written in English were used in this paper. We also limited the publication year of journals from 2010 to 2020. From the results of journal searches, we found around 52.984 journals. However only 5 were included that met the inclusion criteria which were: (1), Randomized Controlled Trial (RCT) that tested the benefits of SSRIs treatment in post-stroke depression patients compared to other antidepressants or other treatment modalities; and (2) provided with the outcome measure of functional independence. In conclusion, we believe that SSRIs have an effect on improving functional independence in post-stroke depression patients. SSRIs have also been shown to have positive effects with various combinations of non-pharmacological therapeutic modalities as their support.